Aperture testing method of hard carbon negative electrode material and application of aperture testing method
By preparing and identifying caramel stock solution, preparing a caramel solution with gradient concentration, and combining two centrifugal separation techniques, the problem of inaccurate pore size testing of hard carbon negative electrode materials is solved, and the accurate characterization of the pore size performance of hard carbon materials is achieved.
Patent Information
- Application Number
- CN202411548740.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-25
AI Technical Summary
The existing caramel decolorization rate testing method is not suitable for hard carbon anode materials, resulting in inaccurate test results, and the number of mesoporous pores of hard carbon anode materials is less than that of activated carbon, making it difficult to conduct accurate pore size testing through traditional methods.
Use glucose to prepare alkaline caramel stock solution and identify it through potassium dichromate standard solution to ensure that the concentration range of caramel stock solution is suitable. Then, a caramel solution with a gradient concentration was prepared, its absorbance was measured, and a standard curve of caramel solution concentration-absorbance was established. The hard carbon sample and caramel solution were separated by two centrifugation, and the caramel decolorization rate was calculated to characterize the pore size performance of the hard carbon material.
Accurate testing of the pore size of hard carbon negative electrode materials and characterization of mesoporous development levels are achieved, which simplifies the testing process and improves the testing accuracy.
Smart Images

Figure BDA0005114510010000021 
Figure BDA0005114510010000081 
Figure BDA0005114510010000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material testing, and in particular to a pore size testing method for hard carbon negative electrode materials and an application thereof. Background Art
[0002] Physical adsorption is the main method for studying the pore size of powder, block, and film samples, including two test methods: gas and liquid adsorption. The current liquid adsorption methods for activated carbon pore size include iodine value, methylene blue value, molasses value, and caramel decolorization rate. These indicators can not only evaluate the adsorption performance of the material, but also be used to evaluate the pore size of the material. Among them, the caramel decolorization rate refers to the ratio of the amount of caramel removed after decolorization to the original sample amount under certain test conditions using the porosity of activated carbon. The caramel decolorization rate is usually used to characterize the degree of mesoporous development of activated carbon.
[0003] Compared with activated carbon materials, hard carbon negative electrode materials refer to carbon that is difficult to graphitize. They are thermal decomposition products of high molecular polymers. Hard carbon negative electrode materials also have a certain number of pore structures, specific surface areas and chemical groups. The number of pores in hard carbon negative electrode materials is closely related to their electrical properties. Therefore, it is necessary to test and evaluate the pore structure of hard carbon negative electrode materials to expand their application prospects in sodium ion batteries. However, there are currently few pore size test methods for hard carbon negative electrode materials. In addition, due to the small particles of hard carbon negative electrode materials, when testing the caramel decolorization rate, filtering through filter paper will cause the hard carbon negative electrode materials to enter the caramel filtrate, resulting in inaccurate test results. At the same time, the number of mesopores in hard carbon negative electrode materials is less than that of activated carbon, and the amount of caramel adsorption is less. After the caramel solution is decolorized, the absorbance value of the caramel filtrate is still greater than 1. It is impossible to calculate the concentration of the caramel filtrate according to Beer's law, which makes the test results inaccurate. Therefore, the current caramel decolorization rate test method for activated carbon is not suitable for testing hard carbon negative electrode materials. Summary of the invention
[0004] In view of the above problems, the present invention discloses a pore size testing method for hard carbon negative electrode materials and its application. The testing method of the present invention can test the pore size of hard carbon materials and characterize the degree of mesopore development, and the test is simple and accurate.
[0005] To achieve the above object, the present invention discloses a pore size testing method for a hard carbon negative electrode material, comprising:
[0006] (1) Preparation of caramel stock solution
[0007] Glucose is used to prepare an alkaline caramel stock solution;
[0008] (2) Preparation of potassium dichromate standard solution
[0009] (3) Identification of caramel solution
[0010] The caramel stock solution is diluted and prepared into a caramel solution, and the absorbance A1 is measured at a wavelength of 426 nm, and the absorbance A2 of the potassium dichromate standard solution at a wavelength of 426 nm is tested. If |A1-A2|≤0.03, it means that the caramel stock solution meets the requirements, otherwise the caramel stock solution needs to be re-prepared;
[0011] (4) Preparation of caramel solution concentration-absorbance standard curve
[0012] The caramel stock solution is prepared into a series of caramel solutions with gradient concentrations, the absorbance A is measured at a wavelength of 426 nm and the absorbance A of each caramel solution is ensured to be less than 1, and a standard curve is drawn according to the absorbance A and the concentration to obtain a standard curve formula 1;
[0013] (5) Caramel decolorization rate test
[0014] Take m0g of hard carbon sample and V0mL of caramel solution with a concentration of C0g / L, heat and mix them, take the supernatant after the first centrifugation and centrifuge it for the second time, take V1mL of the supernatant after the second centrifugation and measure the absorbance A at a wavelength of 426nm, calculate the remaining caramel mass m and the caramel decolorization rate M according to formula 1, formula 2 and formula 3,
[0015] Y=aX+b Formula 1
[0016]
[0017] In the formula: Y is absorbance A; a is the slope of the standard curve; X is the concentration of caramel solution, g / L; b is the intercept of the standard curve; m is the mass of caramel in the caramel solution after decolorization, g; M is the decolorization rate of caramel, %; V1 is the volume of caramel solution, mL; m0 is the mass of the hard carbon sample, g; V0 is the volume of caramel solution before decolorization, mL; C0 is the concentration of caramel solution before decolorization, g / L.
[0018] As a technical solution of the present invention, the preparation of the caramel stock solution includes dissolving anhydrous glucose in water under stirring to obtain a sugar solution, stirring and heating the sugar solution until it is slightly boiling, slowly adding anhydrous sodium carbonate, and after heating, the temperature is raised to 100°C to 115°C, adding ammonium chloride, raising the temperature to 120°C to 135°C, keeping the temperature for a certain period of time, adding sodium carbonate solution, and continuously stirring until the foam disappears.
[0019] As a technical solution of the present invention, the concentration of the caramel stock solution is 1.6 g / mL.
[0020] As a technical solution of the present invention, the anhydrous sodium carbonate accounts for 1.0% to 2.0% of the mass of the anhydrous glucose, the ammonium chloride accounts for 1.0% to 2.0% of the mass of the anhydrous glucose, the concentration of the sodium carbonate solution is 0.01g / mL to 0.20g / mL, and the volume is 10mL to 100mL.
[0021] As a technical solution of the present invention, the preparation of the potassium dichromate standard solution includes grinding potassium dichromate, drying it to constant weight, weighing it, adding water to dissolve it, and then constant volume in a volumetric flask to obtain a solution with a concentration of 0.4±0.05 g / L.
[0022] As a technical solution of the present invention, the caramel solution can be prepared by diluting the caramel stock solution with water and fixing the volume, and the absorbance A1 and the absorbance A2 are measured at least 5 times and the average value is taken.
[0023] As a technical solution of the present invention, the concentrations of the caramel solution with gradient concentration are 0.4 g / L, 0.8 g / L, 1.2 g / L, 1.6 g / L, and 2.0 g / L, respectively.
[0024] As a technical solution of the present invention, the hard carbon sample and the caramel solution are mixed in a conical flask and placed in an oil bath for heating, and the conical flask is taken out and shaken at regular intervals to make the sample in the bottle fall into the caramel solution.
[0025] As a technical solution of the present invention, the rotation speed of the first centrifugation is 3000r / min to 5000r / min, the time of the first centrifugation is 10min to 30min, the rotation speed of the second centrifugation is 3000r / min to 5000r / min, and the time of the second centrifugation is 10min to 30min.
[0026] The second aspect of the present invention discloses the application of the pore size test method of hard carbon negative electrode material in the pore size performance evaluation of hard carbon negative electrode material.
[0027] (1) If the caramel decolorization rate M of the hard carbon negative electrode material is less than 5%, it indicates that the mesoporous property of the hard carbon negative electrode material is poor;
[0028] (2) If the caramel decolorization rate M of the hard carbon negative electrode material is greater than or equal to 5% and less than or equal to 10%, it indicates that the mesoporous properties of the hard carbon negative electrode material are average;
[0029] (3) If the caramel decolorization rate M of the hard carbon negative electrode material is greater than 10%, it indicates that the mesoporous performance of the hard carbon negative electrode material is excellent. In the pore size testing method of the hard carbon negative electrode material of the present invention, glucose is used as a raw material and alkaline catalysis can be used to prepare an alkaline caramel stock solution with high pigmentation. The caramel stock solution is identified by a potassium dichromate standard solution to ensure that the concentration range of the caramel stock solution is suitable for meeting the national standard requirements. By preparing a series of caramel solutions with gradient concentrations and an absorbance less than or equal to 1, the concentration of the caramel filtrate can be calculated according to Beer's law, so that a caramel solution concentration-absorbance standard curve can be established and the amount of caramel adsorbed by the hard carbon negative electrode material can be obtained by calculation. In addition, the present invention uses centrifugation for solid-liquid separation before testing. After the first centrifugation is completed, the supernatant is taken for a second centrifugation and then the supernatant is taken for absorbance testing. Through two centrifugations, the hard carbon negative electrode material is separated from the caramel solution, and the absorbance test can be performed more accurately. This can avoid the problem that the use of filter paper in the pore size test of traditional activated carbon materials causes the hard carbon negative electrode material with a smaller size to enter the caramel filtrate, resulting in inaccurate test results. Therefore, based on the use of caramel adsorption to test the pore size of activated carbon, the present invention combines the characteristics of hard carbon materials, and can test the pore size of hard carbon materials and characterize the degree of mesopore development through potassium dichromate identification and two centrifugations. This test is simple and has high test accuracy. DETAILED DESCRIPTION
[0030] The pore size testing method of the hard carbon negative electrode material of the present invention can better test the pore size of the hard carbon material, and the caramel decolorization rate data obtained by the test can characterize the pore size performance of the hard carbon negative electrode material.
[0031] (1) If the caramel decolorization rate M of the hard carbon negative electrode material is less than 5%, it indicates that the mesoporous property of the hard carbon negative electrode material is poor;
[0032] (2) If the caramel decolorization rate M of the hard carbon negative electrode material is greater than or equal to 5% and less than or equal to 10%, it indicates that the mesoporous properties of the hard carbon negative electrode material are average;
[0033] (3) If the caramel decolorization rate M of the hard carbon negative electrode material is greater than 10%, it indicates that the hard carbon negative electrode material has excellent mesoporous properties. The pore size performance and adsorption performance of the hard carbon negative electrode material are consistent. The more caramel decolorization, the stronger the adsorption capacity and the better the pore size performance. The use of the hard carbon negative electrode material as a negative electrode active material of a sodium ion battery can improve the specific capacity, cycle, rate and other performances of the sodium ion battery.
[0034] The pore size testing method of the hard carbon negative electrode material of the present invention mainly includes five steps: (1) preparation of caramel stock solution; (2) preparation of potassium dichromate standard solution; (3) identification of caramel solution; (4) preparation of caramel solution concentration-absorbance standard curve and (5) caramel decolorization rate test.
[0035] Wherein, in step (1), the preparation of caramel stock solution includes dissolving anhydrous glucose in water under stirring to obtain sugar solution, stirring and heating the sugar solution until it is slightly boiling, slowly adding anhydrous sodium carbonate, and after heating, the temperature is raised to 100°C to 115°C, adding ammonium chloride, and the temperature is raised to 120°C to 135°C for a certain period of time, and sodium carbonate solution is added, and the foam disappears. Slowly adding anhydrous sodium carbonate to the slightly boiling sugar solution can adjust the pH value of the reaction system to accelerate the process of caramel reaction, and then heating and adding ammonium chloride. Ammonium chloride and reducing sugar undergo Maillard reaction to generate caramel pigment with better color and stability, and further heating and adding sodium carbonate solution can catalyze the complete conversion of glucose into caramel. The reaction is carried out under stirring to prevent carbonization due to excessive caramel concentration. The concentration of the caramel stock solution is 1.6g / mL. Under this concentration range, it is possible to ensure the preparation of a suitable standard solution concentration to establish a concentration-absorbance standard curve. Anhydrous sodium carbonate accounts for 1.0% to 2.0% of the mass of anhydrous glucose. As an example, the content of anhydrous sodium carbonate can be, but is not limited to, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%. Ammonium chloride accounts for 1.0% to 2.0% of the mass of anhydrous glucose. As an example, the content of ammonium chloride can be, but is not limited to, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%.
[0036] 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%. The concentration of sodium carbonate solution is 0.01g / mL to 0.20g / mL. As an example, the concentration of sodium carbonate solution can be, but not limited to, 0.01g / mL, 0.03g / mL, 0.05g / mL, 0.08g / mL, 0.10g / mL, 0.13g / mL, 0.15g / mL, 0.18g / mL, 0.20g / mL. The volume of sodium carbonate solution is 10mL to 100mL. As an example, the volume can be, but not limited to, 10mL, 20mL, 30mL, 40mL, 50mL, 60mL, 70mL, 80mL, 90mL, 100mL. The amount of the catalyst sodium carbonate added is used to control the reaction speed of the catalysis to avoid over-reaction and excessive caramel concentration and carbonization.
[0037] In step (2), potassium dichromate can be ground into powder using an agate mortar and then dried to constant weight using an electric drying oven at 115±5° C. Potassium dichromate has a distinct and stable color in the solution and can be used as a reference substance to test the accuracy of absorbance.
[0038] In step (3), the caramel stock solution is diluted with water and fixed to volume to prepare a caramel solution. The absorbance A1 and the absorbance A2 are measured at least 5 times and the average value is taken. Before each measurement, the cuvette is rinsed with water several times and dried. After identification, the caramel stock solution that meets the requirements is poured into a stoppered ground-mouth bottle, sealed and stored away from light. Caramel raw material identification is carried out once a month. If the absorbance of the caramel solution differs from that of the potassium dichromate solution by more than 0.03, the caramel stock solution needs to be reconfigured so that the absorbance of the caramel solution differs from that of the potassium dichromate solution by less than or equal to 0.03.
[0039] In step (4), the concentrations of the caramel solution with gradient concentrations are 0.4 g / L, 0.8 g / L, 1.2 g / L, 1.6 g / L, and 2.0 g / L, respectively. When preparing the caramel solution with gradient concentrations, the caramel stock solution is dissolved in water and transferred to a 500 mL volumetric flask, the beaker is rinsed three times and then fixed to volume, and ultrapure water is used for blank calibration, thereby testing the absorbance at each concentration and preparing a caramel solution concentration-absorbance standard curve.
[0040] In step (5), the hard carbon sample and the caramel solution are mixed in a conical flask and placed in an oil bath for heating. The conical flask is taken out and shaken at regular intervals to allow the sample on the bottle body to fall into the caramel solution. The temperature in the oil bath is set to 100°C, and the temperature probe is placed in the oil bath. After the temperature reaches 100°C, the conical flask is placed in the oil bath and heated for 30 minutes. During this period, the conical flask is taken out every 5 minutes and shaken to shake the sample on the bottle wall into the solution. After heating is completed, the conical flask is taken out, the silicone oil on the bottle body is wiped clean, and the mixed solution is immediately poured into a centrifuge tube. The speed of the first centrifugation is 3000r / min to 5000r / min, and the centrifugation time is 10min to 30min. As an example, the speed of the first centrifugation can be, but is not limited to, 3000 r / min, 3200 r / min, 3400 r / min, 3600 r / min, 3800 r / min, 4000 r / min, 4200 r / min, 4400 r / min, 4600 r / min, 4800 r / min, 5000 r / min, and the time of centrifugation can be, but is not limited to, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min. The speed of the second centrifugation is 3000 r / min to 5000 r / min, and the time of the second centrifugation is 10 min to 30 min. As an example, the rotation speed of the second centrifugation can be but is not limited to 3000r / min, 3200r / min, 3400r / min, 3600r / min, 3800r / min, 4000r / min, 4200r / min, 4400r / min, 4600r / min, 4800r / min, 5000r / min, and the centrifugation time can be but is not limited to 10min, 12min, 14min, 16min, 18min, 20min, 22min, 24min, 26min, 28min, 30min.
[0041] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0042] Example 1
[0043] This embodiment is to test the pore size of the hard carbon negative electrode material A, and the testing method includes the following steps. The hard carbon negative electrode material A is tested by a pore size analyzer, and the pore volume of the mesopores between 1.7nm and 300.0nm is 0.052250cm 3 / g.
[0044] (1) Preparation of caramel stock solution
[0045] Add 200mL of ultrapure water to the three-necked flask, add 300g of anhydrous glucose while stirring until the anhydrous glucose is completely dissolved, place the three-necked flask on a heating jacket, set the temperature to 105°C, insert the electric stirrer paddle and the heating jacket temperature probe into the three-necked flask, heat and stir until the sugar solution is slightly boiling, set the heating jacket temperature to 110°C within 30min, and then slowly add 5g of anhydrous sodium carbonate to the sugar solution. After the sugar solution temperature reaches 110°C, slowly add 5g of ammonium chloride, set the heating jacket temperature to heat to 125°C within 25min, keep warm for 35min after reaching 125°C, then slowly add 50mL of 0.1g / mL sodium carbonate solution to the sugar solution, and keep stirring until the foam disappears.
[0046] (2) Preparation of potassium dichromate standard solution
[0047] Grind potassium dichromate in an agate mortar and dry it in an electric drying oven adjusted to (115±5)℃ to constant weight. Weigh 0.420g of potassium dichromate, dissolve it in water, and transfer it to a 1000ml volumetric flask to make up the volume.
[0048] (3) Identification of caramel solution
[0049] Use a beaker to weigh 0.833g of caramel stock solution, add water to dissolve and transfer to a 500mL volumetric flask, rinse the beaker three times and then make up the volume. Measure the absorbance of the prepared caramel solution at a wavelength of 426nm, record the data, measure the same solution 6 times and take the average value. Then pour out the solution in the cuvette, wash the cuvette with ultrapure water, blow dry, add potassium dichromate solution, measure the absorbance, record the data, measure the same solution 6 times and take the average value. Compare the absorbance of the caramel solution with that of the potassium dichromate solution. If the difference between the absorbances of the two is less than 0.03, it means that the caramel stock solution meets the requirements. Pour it into a stoppered ground-mouth bottle and seal it to avoid light. Caramel raw material identification is carried out once a month. If the absorbance of the caramel solution differs from that of the potassium dichromate solution by more than 0.03, the caramel stock solution needs to be reconfigured.
[0050] (4) Preparation of caramel solution concentration-absorbance standard curve
[0051] Take 0.2g, 0.4g, 0.6g, 0.8g, and 1.0g of caramel stock solution, dissolve in water, transfer to a 500mL volumetric flask, rinse the beaker three times and adjust the volume to prepare a caramel solution with gradient concentrations of 0.4g / L, 0.8g / L, 1.2g / L, 1.6g / L, and 2.0g / L. Use ultrapure water as blank calibration, measure the absorbance of each concentration of caramel stock solution at a wavelength of 426nm, record the data and draw a standard curve. The standard curve is calculated according to the formula:
[0052] Y=0.4049X
[0053] (5) Caramel decolorization rate test
[0054] Weigh 0.400 g of the hard carbon negative electrode material A that has been dried through a 200-mesh sieve, use a pipette to absorb 25 mL of 1.6 g / L caramel solution, transfer it into a conical flask, shake the conical flask to mix the sample and caramel solution evenly, turn on the oil bath, set the temperature to 100 °C, put the temperature probe into the oil bath, and when the temperature reaches 100 °C, put the conical flask into the oil bath and heat for 30 min. Take out the conical flask every 5 min, shake the conical flask to shake the sample on the bottle wall into the solution, take out the conical flask after heating is completed, and wipe the bottle clean. of silicone oil, and immediately pour the mixture into a centrifuge tube, centrifuge at 4000r / min for 15min, take it out after centrifugation, use a rubber-tipped dropper to take 15mL of supernatant, transfer it to another centrifuge tube, centrifuge again at 4000r / min for 15min, after centrifugation, use a rubber-tipped dropper to take the supernatant in the centrifuge tube after the second centrifugation and move it to a blank-calibrated cuvette, perform absorbance test at a wavelength of 426nm, and measure the absorbance. Repeat the test 6 times, and the results are shown in Table 1.
[0055] Table 1 Absorbance and caramel decolorization rate data of hard carbon negative electrode material A
[0056]
[0057] Example 2
[0058] This embodiment is to test the pore size of the hard carbon negative electrode material B, and the testing method includes the following steps. The hard carbon negative electrode material B is tested by a pore size analyzer, and the pore volume of the mesopores between 1.7nm and 300.0nm is 0.065378cm 3 / g.
[0059] (1) Preparation of caramel stock solution
[0060] Add 200mL of ultrapure water to the three-necked flask, add 300g of anhydrous glucose while stirring until the anhydrous glucose is completely dissolved, place the three-necked flask on a heating jacket, set the temperature to 105°C, insert the electric stirrer paddle and the heating jacket temperature probe into the three-necked flask, heat and stir until the sugar solution is slightly boiling, set the heating jacket temperature to 110°C within 30min, and then slowly add 5g of anhydrous sodium carbonate to the sugar solution. After the sugar solution temperature reaches 110°C, slowly add 5g of ammonium chloride, set the heating jacket temperature to heat to 125°C within 25min, keep warm for 35min after reaching 125°C, then slowly add 50mL of 0.1g / mL sodium carbonate solution to the sugar solution, and keep stirring until the foam disappears.
[0061] (2) Preparation of potassium dichromate standard solution
[0062] Grind potassium dichromate in an agate mortar and dry it in an electric drying oven adjusted to (115±5)℃ to constant weight. Weigh 0.420g of potassium dichromate, dissolve it in water, and transfer it to a 1000ml volumetric flask to make up the volume.
[0063] (3) Identification of caramel solution
[0064] Use a beaker to weigh 0.833g of caramel stock solution, add water to dissolve and transfer to a 500mL volumetric flask, rinse the beaker three times and then make up the volume. Measure the absorbance of the prepared caramel solution at a wavelength of 426nm, record the data, measure the same solution 6 times and take the average value. Then pour out the solution in the cuvette, wash the cuvette with ultrapure water, blow dry, add potassium dichromate solution, measure the absorbance, record the data, measure the same solution 6 times and take the average value. Compare the absorbance of the caramel solution with that of the potassium dichromate solution. If the difference between the absorbances of the two is less than 0.03, it means that the caramel stock solution meets the requirements. Pour it into a stoppered ground-mouth bottle and seal it to avoid light. Caramel raw material identification is carried out once a month. If the absorbance of the caramel solution differs from that of the potassium dichromate solution by more than 0.03, the caramel stock solution needs to be reconfigured.
[0065] (4) Preparation of caramel solution concentration-absorbance standard curve
[0066] Take 0.2g, 0.4g, 0.6g, 0.8g, and 1.0g of caramel stock solution, dissolve in water, transfer to a 500mL volumetric flask, rinse the beaker three times and adjust the volume to prepare a caramel solution with gradient concentrations of 0.4g / L, 0.8g / L, 1.2g / L, 1.6g / L, and 2.0g / L. Use ultrapure water as blank calibration, measure the absorbance of each concentration of caramel stock solution at a wavelength of 426nm, record the data and draw a standard curve. The standard curve is calculated according to the formula:
[0067] Y=0.4049X
[0068] (5) Caramel decolorization rate test
[0069] Weigh the hard carbon negative electrode material B 0.400 after drying through a 200-mesh sieve, use a pipette to absorb 25 mL of 1.6 g / L caramel solution, transfer it into a conical flask, shake the conical flask to mix the sample and caramel solution evenly, turn on the oil bath, set the temperature to 100 ° C, put the temperature probe into the oil bath, and when the temperature reaches 100 ° C, put the conical flask into the oil bath and heat for 30 minutes. Take out the conical flask every 5 minutes, shake the conical flask to shake the sample on the bottle wall into the solution, take out the conical flask after heating is completed, and wipe the bottle clean. Silicone oil, and immediately pour the mixture into a centrifuge tube, centrifuge at 4000r / min for 15min, take it out after centrifugation, use a rubber-tipped dropper to take 15mL of supernatant, transfer it to another centrifuge tube, centrifuge again at 4000r / min for 15min, after centrifugation, use a rubber-tipped dropper to take the supernatant in the centrifuge tube after the second centrifugation and move it to a blank calibrated cuvette, perform absorbance test at a wavelength of 426nm, and measure the absorbance. Repeat the test 6 times, and the results are shown in Table 2.
[0070] Table 2 Absorbance and caramel decolorization rate data of hard carbon negative electrode material B
[0071]
[0072] Comparative Example 1
[0073] This comparative example tests the pore size of the hard carbon negative electrode material A, and the testing method includes the following steps. The hard carbon negative electrode material A is tested by a pore size analyzer, and the pore volume of the mesopores between 1.7 nm and 300.0 nm is 0.052250 cm 3 / g.
[0074] (1) Preparation of caramel stock solution
[0075] Add 200mL of ultrapure water to the three-necked flask, add 300g of anhydrous glucose while stirring until the anhydrous glucose is completely dissolved, place the three-necked flask on a heating jacket, set the temperature to 105°C, insert the electric stirrer paddle and the heating jacket temperature probe into the three-necked flask, heat and stir until the sugar solution is slightly boiling, set the heating jacket temperature to 110°C within 30min, and then slowly add 5g of anhydrous sodium carbonate to the sugar solution. After the sugar solution temperature reaches 110°C, slowly add 5g of ammonium chloride, set the heating jacket temperature to heat to 125°C within 25min, keep warm for 35min after reaching 125°C, then slowly add 50mL of 0.1g / mL sodium carbonate solution to the sugar solution, and keep stirring until the foam disappears.
[0076] (2) Preparation of potassium dichromate standard solution
[0077] Grind potassium dichromate in an agate mortar and dry it in an electric drying oven adjusted to (115±5)℃ to constant weight. Weigh 0.420g of potassium dichromate, dissolve it in water, and transfer it to a 1000ml volumetric flask to make up the volume.
[0078] (3) Identification of caramel solution
[0079] Use a beaker to take 0.833g of caramel stock solution, add water to dissolve and transfer to a 500mL volumetric flask, rinse the beaker three times and then make up the volume; measure the absorbance of the prepared caramel solution at a wavelength of 426nm, record the data, measure the same solution 6 times and take the average value. Then pour out the solution in the cuvette, wash the cuvette with ultrapure water, blow dry, add potassium dichromate solution, measure the absorbance, record the data, and measure the same solution 6 times. Compare the absorbance of the caramel solution with that of the potassium dichromate solution. If the difference between the absorbances of the two is less than 0.03, it means that the caramel stock solution meets the requirements. Pour it into a stoppered ground-mouth bottle and seal it to avoid light. Caramel raw material identification is carried out once a month. If the absorbance of the caramel solution differs from that of the potassium dichromate solution by more than 0.03, the caramel stock solution needs to be reconfigured.
[0080] (4) Preparation of caramel test solution
[0081] Take 17g of caramel stock solution, dissolve it in water and transfer it into a 500mL volumetric flask, dilute to scale and shake well. The caramel concentration of the solution is 34g / L.
[0082] (5) Preparation of blank test solution
[0083] Take 1g of caramel stock solution, dissolve it in water, transfer it into a 500mL volumetric flask, dilute to the mark, and shake well. The caramel concentration of the solution is 2g / L.
[0084] (6) Caramel decolorization rate test
[0085] Weigh the hard carbon negative electrode material A 0.400 after drying through a 200 mesh sieve, use a pipette to absorb 25mL of a caramel solution with a concentration of 34g / L and move it into a conical flask, shake the conical flask to mix the sample and the caramel solution evenly, turn on the oil bath, set the temperature to 100°C, put the temperature probe into the oil bath, and after the temperature reaches 100°C, put the conical flask into the oil bath and heat for 30min, take out the conical flask every 5min, shake the conical flask, and shake the sample on the bottle wall into the solution. After heating, take out the conical flask, wipe the silicone oil on the bottle, filter it immediately with filter paper, discard 5mL of the initial filtrate, filter all the test liquid, and cool it to room temperature. Measure the absorbance value at a wavelength of 426nm. Absorb the blank test solution, filter it, and measure the absorbance value at a wavelength of 426nm. Calculate the caramel decolorization rate according to the following formula, and the results are shown in Table 3.
[0086] The caramel decolorization rate is expressed as mass fraction w, the value is expressed as %, and is calculated according to formula 4.
[0087] Where: ρ0——caramel concentration in caramel test solution, g / L;
[0088] ρ——caramel concentration in blank test solution, g / L;
[0089] A x ——Absorbance value of caramel filtrate
[0090] A——Absorbance value of blank filtrate after filtration
[0091]
[0092] Table 3 Absorbance and caramel decolorization rate data of hard carbon negative electrode material A
[0093]
[0094] Comparative Example 2
[0095] This comparative example tests the pore size of the hard carbon negative electrode material B, and the testing method includes the following steps. The hard carbon negative electrode material B is tested by a pore size analyzer, and the pore volume of the mesopores between 1.7 nm and 300.0 nm is 0.065378 cm 3 / g.
[0096] (1) Preparation of caramel stock solution
[0097] Add 200mL of ultrapure water to the three-necked flask, add 300g of anhydrous glucose while stirring until the anhydrous glucose is completely dissolved, place the three-necked flask on a heating jacket, set the temperature to 105°C, insert the electric stirrer paddle and the heating jacket temperature probe into the three-necked flask, heat and stir until the sugar solution is slightly boiling, set the heating jacket temperature to 110°C within 30min, and then slowly add 5g of anhydrous sodium carbonate to the sugar solution. After the sugar solution temperature reaches 110°C, slowly add 5g of ammonium chloride, set the heating jacket temperature to heat to 125°C within 25min, keep warm for 35min after reaching 125°C, then slowly add 50mL of 0.1g / mL sodium carbonate solution to the sugar solution, and keep stirring until the foam disappears.
[0098] (2) Preparation of potassium dichromate standard solution
[0099] Grind potassium dichromate in an agate mortar and dry it in an electric drying oven adjusted to (115±5)℃ to constant weight. Weigh 0.420g of potassium dichromate, dissolve it in water, and transfer it to a 1000ml volumetric flask to make up the volume.
[0100] (3) Identification of caramel solution
[0101] Use a beaker to take 0.833g of caramel stock solution, add water to dissolve and transfer to a 500mL volumetric flask, rinse the beaker three times and then make up the volume; measure the absorbance of the prepared caramel solution at a wavelength of 426nm, record the data, measure the same solution 6 times and take the average value. Then pour out the solution in the cuvette, wash the cuvette with ultrapure water, blow dry, add potassium dichromate solution, measure the absorbance, record the data, and measure the same solution 6 times. Compare the absorbance of the caramel solution with that of the potassium dichromate solution. If the difference between the absorbances of the two is less than 0.03, it means that the caramel stock solution meets the requirements. Pour it into a stoppered ground-mouth bottle and seal it to avoid light. Caramel raw material identification is carried out once a month. If the absorbance of the caramel solution differs from that of the potassium dichromate solution by more than 0.03, the caramel stock solution needs to be reconfigured.
[0102] (4) Preparation of caramel test solution
[0103] Take 17g of caramel stock solution, dissolve it in water and transfer it into a 500mL volumetric flask, dilute to scale and shake well. The caramel concentration of the solution is 34g / L.
[0104] (5) Preparation of blank test solution
[0105] Take 1g of caramel stock solution, dissolve it in water, transfer it into a 500mL volumetric flask, dilute to the mark, and shake well. The caramel concentration of the solution is 2g / L.
[0106] (6) Caramel decolorization rate test
[0107] Weigh the hard carbon negative electrode material B 0.400 after drying through a 200 mesh sieve, use a pipette to absorb 25mL of a caramel solution with a concentration of 34g / L and move it into a conical flask, shake the conical flask to mix the sample and the caramel solution evenly, turn on the oil bath, set the temperature to 100°C, put the temperature probe into the oil bath, and after the temperature reaches 100°C, put the conical flask into the oil bath and heat for 30min, take out the conical flask every 5min, shake the conical flask, and shake the sample on the bottle wall into the solution. After heating, take out the conical flask, wipe the silicone oil on the bottle, filter it immediately with filter paper, discard 5mL of the initial filtrate, filter all the test liquid, and cool it to room temperature. Measure the absorbance value at a wavelength of 426nm. Absorb the blank test solution, filter it, and measure the absorbance value at a wavelength of 426nm. Calculate the caramel decolorization rate with reference to the following formula, and the results are shown in Table 4.
[0108] The caramel decolorization rate is expressed as mass fraction w, the value is expressed as %, and is calculated according to formula 4.
[0109] Table 4 Absorbance and caramel decolorization rate data of hard carbon negative electrode material B
[0110]
[0111] By comparing Example 1 and Example 2, it can be seen that the caramel decolorization rate of hard carbon negative electrode material A is lower than that of hard carbon negative electrode material B, which indicates that the number of mesopores in hard carbon negative electrode material A is less than that in hard carbon negative electrode material B. This result is consistent with the result obtained by the pore size analyzer. Therefore, the testing method of the present invention can effectively reflect the mesopore data of the hard carbon negative electrode material, which is of practical significance for the characterization of the pore size performance of the hard carbon material.
[0112] By comparing Comparative Example 1 and Comparative Example 2, it can be seen that the caramel decolorization rate of hard carbon negative electrode material A is higher than that of hard carbon negative electrode material B, which indicates that the number of mesopores of hard carbon negative electrode material A is greater than that of hard carbon negative electrode material B, and this result is opposite to the result obtained by the pore size analyzer. This may be because Comparative Examples 1 and 2 use the method of testing the caramel decolorization rate of activated carbon to test the caramel decolorization rate of hard carbon. Since the hard carbon negative electrode material has fewer mesopores than activated carbon, its adsorption of caramel is lower than that of activated carbon, and the hard carbon negative electrode material is smaller than activated carbon. When filtering with filter paper, hard carbon can pass through the filter paper into the filtrate, which ultimately causes the absorbance of the caramel filtrate to be greater than the absorbance of the caramel test solution without adsorption, and the test results are contrary to the test results of the pore size analyzer. And because the absorbance value of the caramel filtrate is greater than 1 and the test solution is a concentrated solution, Beer's theorem is invalid and the adsorption amount of the caramel solution of the hard carbon negative electrode material cannot be calculated based on the absorbance value. Therefore, the result is not accurate and has little significance for the characterization of the pore size performance of the hard carbon material.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Its various test parameters, such as various parameters of pre-treatment and adsorption treatment, can be adaptively adjusted. Ordinary technicians in this field should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for testing the pore size of a hard carbon negative electrode material, characterized in that: include: (1) Preparation of caramel stock solution Glucose is used to prepare an alkaline caramel stock solution; (2) Preparation of potassium dichromate standard solution (3) Identification of caramel solution The caramel stock solution is diluted and prepared into a caramel solution, and the absorbance A1 is measured at a wavelength of 426 nm, and the absorbance A2 of the potassium dichromate standard solution at a wavelength of 426 nm is tested. If |A1-A2|≤0.03, it means that the caramel stock solution meets the requirements, otherwise the caramel stock solution needs to be re-prepared; (4) Preparation of caramel solution concentration-absorbance standard curve The caramel stock solution is prepared into a series of caramel solutions with gradient concentrations, the absorbance A is measured at a wavelength of 426 nm and the absorbance A of each caramel solution is ensured to be less than 1, and a standard curve is drawn according to the absorbance A and the concentration to obtain a standard curve formula 1; (5) Caramel decolorization rate test Take m0g of hard carbon sample and V0mL of caramel solution with a concentration of C0g / L, heat and mix them, take the supernatant after the first centrifugation and centrifuge it for the second time, take V1mL of the supernatant after the second centrifugation and measure the absorbance A at a wavelength of 426nm, calculate the remaining caramel mass m and the caramel decolorization rate M according to formula 1, formula 2 and formula 3, Y=aX+b Formula 1 Where: Y is absorbance A; a is the slope of the standard curve; X is the concentration of caramel solution, g / L; b is the intercept of the standard curve; m is the mass of caramel in the decolorized caramel solution, g; M is the caramel decolorization rate, %; V1 is the volume of caramel solution, mL; m0 is the mass of hard carbon sample, g; V0 is the volume of caramel solution before decolorization, mL; C0 is the concentration of caramel solution before decolorization, g / L.
2. According to the pore size testing method for hard carbon negative electrode materials according to claim 1, the preparation of the caramel stock solution includes dissolving anhydrous glucose in water under stirring to obtain a sugar solution, stirring and heating the sugar solution until it is slightly boiling, slowly adding anhydrous sodium carbonate, and after heating, the temperature is raised to 100°C to 115°C, adding ammonium chloride, raising the temperature to 120°C to 135°C, keeping the reaction for a certain period of time, adding sodium carbonate solution, and stirring continuously until the foam disappears.
3. The pore size testing method of hard carbon negative electrode material according to claim 2, characterized in that: The concentration of the caramel stock solution is 1.6 g / mL.
4. The pore size testing method of hard carbon negative electrode material according to claim 2, characterized in that: The anhydrous sodium carbonate accounts for 1.⊙% to 2.⊙% of the mass of the anhydrous glucose, the ammonium chloride accounts for 1.⊙% to 2.⊙% of the mass of the anhydrous glucose, the concentration of the sodium carbonate solution is 0.01g / mL to 0.20g / mL, and the volume is 10mL to 100mL.
5. The pore size testing method of hard carbon negative electrode material according to claim 1, characterized in that: The preparation of the potassium dichromate standard solution includes grinding potassium dichromate, drying it to constant weight, weighing it, adding water to dissolve it, and then constant volume in a volumetric flask to obtain a solution with a concentration of 0.4±⊙.05 g / L.
6. The pore size testing method of hard carbon negative electrode material according to claim 1, characterized in that: The caramel solution can be prepared by diluting the caramel stock solution with water and fixing the volume. The absorbance A1 and the absorbance A2 are measured at least 5 times and the average values are taken.
7. The pore size testing method of hard carbon negative electrode material according to claim 1, characterized in that: The concentrations of the caramel solution with gradient concentration are 0.4 g / L, ⊙.8 g / L, 1.2 g / L, 1.6 g / L, and 2.⊙ g / L respectively.
8. The pore size testing method of hard carbon negative electrode material according to claim 1, characterized in that: The hard carbon sample and the caramel solution are mixed in a conical flask and placed in an oil bath for heating. The conical flask is taken out and shaken at regular intervals to make the sample in the flask fall into the caramel solution.
9. The pore size testing method of hard carbon negative electrode material according to claim 1, characterized in that: The speed of the first centrifugation is 3000 r / min to 5000 r / min, and the time of the first centrifugation is 10 min to 30 min. The speed of the second centrifugation is 3000 r / min to 5000 r / min, and the time of the second centrifugation is 10 min to 30 min.
10. Application of the pore size testing method for hard carbon negative electrode materials according to any one of claims 1 to 9 in pore size performance evaluation of hard carbon negative electrode materials, characterized in that: (1) If the caramel decolorization rate M of the hard carbon negative electrode material is less than 5%, it indicates that the mesoporous property of the hard carbon negative electrode material is poor; (2) If the caramel decolorization rate M of the hard carbon negative electrode material is greater than or equal to 5% and less than or equal to 10%, it indicates that the mesoporous properties of the hard carbon negative electrode material are average; (3) If the caramel decolorization rate M of the hard carbon negative electrode material is greater than 10%, it indicates that the hard carbon negative electrode material has excellent mesoporous properties.
Citation Information
Cited By
Evaluation method for pore distribution of hard carbon
CN120801139A